Indirect Costs of Financial Distress and Bankruptcy Law: Evidence from Trade Credit and Sales - Sautner, Zacharias; Vladimirov, Vladimir (Review of Finance, 2018)
We argue that stronger debt enforcement in bankruptcy can reduce indirect costs of financial distress: (i) by increasing the likelihood of restructuring outside bankruptcy and (ii) by improving the recovery rate of stakeholders, such as trade creditors, through explicit legal provisions. Consistent with these predictions, we find that when debt enforcement is stronger, financially distressed firms are less exposed to indirect distress costs in the form of reduced access to trade credit and forgone sales. We document these effects in a panel of firms from forty countries with heterogeneous debt enforcement characteristics and in differences-in-differences tests exploiting several recent bankruptcy reforms.